'Hydro‐point' – The forgotten and unspoken entity in hydropneumothorax. Issue 4 (29th June 2021) - Mahalingam, Sasikumar; Rajendran, Gunaseelan; Nathan, Balamurugan; Kugan, Ezhil; Sadasivam, Anuusha
Abstract: Effusive pneumothorax is an abnormal collection of air and fluid within the pleural space: blood, pus, or serous fluid. Thus, effusive pneumothorax can be categorized as hemopneumothorax, pyopneumothorax, or hydropneumothorax, depending on the type of fluid accumulation. Hydropneumothorax is a clinical condition defined by the presence of air and serous fluid within the pleura space. Hydropneumothorax is one of the common respiratory emergencies encountered in the emergency department in India. Etiologies can be classified into infectious and non‐infectious causes, among which tuberculosis being the most common one. Point of care ultrasound (POCUS) can help diagnose hydropneumothorax at the bedside rather than shift the patient for an X‐ray. Here, we describe a case of hydropneumothorax, which was diagnosed using POCUS by characteristic sonographic signs, namely "Hydro‐point" and "barcode‐hydro point‐sinusoidal sign." Sonographic hydro‐point is the transition zone of the air‐fluid interface, which is seen in hydropneumothorax. Targhetta et al., in 1992, introduced the term "Hydro‐point" in lung ultrasound for diagnosing hydropneumothorax but has been under‐reported/unspoken much in the literature. With the use of POCUS, we diagnosed and stabilized the patient in the Emergency Department.